Investigation of Tetra(p-carboxyphenyl)porphyrin in Monomer and Aggregation Forms by UV-Vis, 1H NMR, 13C NMR, SEM and Atomic Force Microscopy - RAHIMI, RAHMATOLLAH; MOHARRAMI, FARIBA; HAMED RAHMANPOUR, SEYED (Asian Journal of Chemistry, 2010)
Tetra(p-carboxyphenyl)porphyrin (H2TCPP) was synthesized and characterized by UV-Vis, 1H NMR, 13C NMR and SEM spectroscopy. The porphyrin H2TCPP aggregated and formed nanorods and nanorings on silica in aqueous acidic solution (HCl). These rods of tetra(p-carboxyphenyl) porphyrin were investigated by UV-visible spectroscopy and atomic force microscopy in aqueous acidic solution.